Pengaruh Brand Image, Harga, dan Label Halal Dalam Keputusan Pembelian Produk Kosmetik Wardah di Kudus - Kunasari, Kunasari; Dhia R.A., Salsabila; Nikmah, Zahrotun; Andni, Riyan; Candra, Eki (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to determine the influence of brand image, price, and halal labels in the purchase decision of wardah cosmetic products in Kudus City. Wardah cosmetic products that always occupy the top brands in Indonesia show that many use this product. So that many consumers already believe in Wardah cosmetic products. In this study, a questionnaire was distributed to all people in the holy city with a sample of 125 respondents. And the data was calculated using SPSS version 20. Where the brand image is (X1), price (X2), halal label (X3) and purchase decision (Y). And this study aims to show whether brand image has a significant influence on the purchase decision of Wardah cosmetic products, whether price has a significant influence on the purchase decision of Wardah cosmetic products, and whether halal labels have a significant influence on the purchase decision of Wardah cosmetic products.